Economic analysis of the maintenance of Cenchrus purpureus germplasm bank of the Institute of Animal Science - Abreu Cruz, Amanda; Hernández Montesinos, A.R; Báez Quiñones, Nadia; Rodríguez Alfonso, Daymara; Fortes González, Dayleni; Herrera, R.S. (Cuban Journal of Agricultural Science, 2024)
The maintenance of the Cenchrus purpureus germplasm collection of the Institute of Animal Science of the Republic of Cuba was economically analyzed. For the research, the direct costs involved in maintaining the accessions of the germplasm bank were considered. Annual cultural maintenance labors were taken into account. The accumulation of expenses was prepared, in Cuban pesos, based on the investment in salary, fuel, machinery and other inputs. In the analysis, a total annual expense of $45,840.66 Cuban pesos was found. Of the total expenses, salary and other inputs constituted the largest outlay, with $29,260.01 and $10,350.56 Cuban pesos, respectively. The maintenance labors with the highest expenses were the cleaning of plots, mechanical control of weeds and irrigation. It is concluded that it is necessary to make modifications in the schedule of annual cultural labors to reduce expenses in salary and other inputs.